Cross-sectional investigation of mycological diagnosis challenges in Saudi Arabia - Khateb, Aiah Mustafa; Alkhaibari, Shatha Ali (Frontiers in Cellular and Infection Microbiology, 2023)
Aiah M Khateb1,2, Shatha Ali Alkhaibari1 1Department of Medical Laboratory Technology, Collage of Applied Medical Science, Taibah University, P.O.Box 344, Medina 42353, Saudi Arabia 2Special Infectious Agents Unit, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, Saudi Arabia * Correspondence: Dr. Aiah M. Khateb,AKHATEB@taibahu.edu.sa,Tel.: +966565932330, ORCID ID: 0000-0002-7806-8748 Keywords: Fungal; Saudi Arabia; diagnosis; mycology; challenges; Mold; Morphology; Yeast; Candida; Aspergillus. Number of words 3523, number of figures 1, number of tables 2 Abstract Background: Global incidence of fungal infection has increased dramatically over the previous two-decades. Fungal diseases are threatening to both immunocompetent, and immunocompromised patients. The necessity to evaluate the current fungal diagnostics status in Saudi Arabia is highly required, especially with the increase of immunosuppressed population. This cross-sectional study investigated the gaps of mycological diagnosis on a national level. Materials and methods call interview questionnaire responses were collected to evaluate the fungal assays demand, diagnostic methods’ quality, and mycological expertise of laboratories workers in both public and private medical intuitions. Data were analyzed using (IBM SPSS ® software version 22.0). Results total of 57 hospitals from all Saudi regions participated in the questionnaire, however only 32% received or processed mycological samples. Most participants were from Mecca region (25%), Riyadh region (19%), Eastern region (14%). Top fungal isolates identified were Candida spp., Aspergillus spp. and dermatophyte. Fungal investigation is highly requested by Intensive care, dermatology, and Obstetrics & Gynecology units. Most laboratories rely on fungal culture, and microscopic examination which mostly identify Candida to the genus level. Most laboratories use 37C incubators for culture (67%). Antifungal susceptibility testing (AST), serological and molecular methods were rarely performed and mostly outsourced. Using accurate identification and AST were the primary factors to improve fungal diagnosis among turnaround time and cost. Three major obstacles were identified as availability of; facility (47%), reagents and kits (32%) and good training (21%). Conclusions The results indicated fungal diagnosis demand was relatively higher in high population regions. This study highlighted the gaps in fungal diagnostics and the need for reference laboratory to improve it in Saudi hospitals.